2020
DOI: 10.1177/0014402920969187
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tier 2 Mathematics Interventions for Students With Mathematics Difficulties: A Meta-Analysis

Abstract: This meta-analysis examined the effectiveness of supplemental Tier 2 mathematics interventions for students with mathematics difficulties (MD). We reviewed 39 experimental and quasiexperimental studies that included 40 independent samples, with 61 treatment groups. Utilizing robust variance estimation (RVE), results revealed a treatment effect of 0.41. Mixed-effects meta-regression analyses revealed that Tier 2 interventions were moderated by participants’ MD status, grade level of subjects, intervention model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 79 publications
4
38
0
Order By: Relevance
“…In contrast, Jitendra et al. (2020) found no moderating effect for instructional time. These incongruent results may be due to differences in variable specification across studies; while Jitendra et al.…”
Section: Performance and Classification Of Students With MDmentioning
confidence: 89%
See 4 more Smart Citations
“…In contrast, Jitendra et al. (2020) found no moderating effect for instructional time. These incongruent results may be due to differences in variable specification across studies; while Jitendra et al.…”
Section: Performance and Classification Of Students With MDmentioning
confidence: 89%
“…Recently, results of four relevant meta‐analytic reviews focusing on secondary students with MD (i.e., Hughes et al., 2014; Jitendra et al., 2018; Jitendra et al., 2020; Stevens et al., 2018) provide empirical support for the efficacy of math interventions. Across these studies, researchers found positive impacts for interventions with effect sizes (ESs) ranging from moderate to large, g = 0.37 to 0.85, suggesting considerable variation across effects of interventions.…”
Section: Performance and Classification Of Students With MDmentioning
confidence: 99%
See 3 more Smart Citations